COGNITIVE-MNESTIC FUNCTIONS IN PATIENTS SUFFERING FROM HYPERTENSIVE DISEASE WITH HYPOTHYROIDISM COMORBIDITY - Лесів, М. І.; Гриб, В. А.; Дорошенко, О. О.; Коваль, М. В.; Максимчук, Л. Т. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Theaim of the work was to analyze cognitive disorders in patients with hypertensive disease and those with hyperthyroidism as well as in patients suffering from combined pathology – hypertension with comorbid hyperthyroidism. 26 patients have been in vestigated with thehelp of MoCA scale. There sults show in significant difference (р>0,05) in comparison with cognitive disorders in patients with hypertensivedisease, those with hyperthyroidism as well as those with comorbidpathology: combination of hypertension with hyperthyroidism. Thus, more sensitive scales are required to evaluate cognitive dysfunction in accordance with certain domainsto assess the differential therapy tactics.